Implementasi Pembelajaran Kewirausahaan Dalam Menumbuhkan Minat Berwirausaha Mahasiswa - Martini Martini; Azizah Zein; Nurul Azmi Pasaribu; Mansur Keling (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
Entrepreneurship education not only provides a theoretical basis for the concept of entrepreneurship, but can also shape students’ thought patterns, behavior and views about entrepreneurship. .This research aims to determine the concept of entrepreneurship education, the implementation of entrepreneurship education in lectures to foster interest in entrepreneurship in students, the benefits of entrepreneurship lectures for students. .This research is a type of qualitative research, a research process that produces descriptive data about the behavior of people being observed in the form of written words. Expanded inductive analysis to discover the true meaning of the phenomenon under study. .The results of this research have a positive impact on students by providing entrepreneurial skills, increasing entrepreneurial insight, forming motivation, and training mentally when doing business.